Correction of the cytomorphological changes by the quercetin in the mucous membrane of the mouth cavity of rats under the action of systemic pathogenic factors - S. A. Schnaider; A. V. Parasyuk; A. V. Skiba; E. K. Tkachenko (Kazimierz Wielki University, 2017)
The purpose of this research was to study the correction by the quercetin of the structural and functional changes in the mucous membrane of the mouth cavity of rats caused by the action of the doxaglide prooxidant and chronic emotional and painful stress in conditions of nutritional deficiencies in plant components. The  research  was  conducted  on 21 rats 1.5 months. age. The duration of the experiment was 60 days. Intact group (1) consisted of 7 rats, which were kept on a standard ration of the vivarium. In the 2nd group (7 rats), after 1 month of their non-polifenol diet were subjected to the combined effects of the delagil oral injections (5 mg / kg) and chronic emotional and pain stress. The protective effects of the quercetin have been studied with the combined effects of delagil, chronic stress and non-polifenol diet. Rats of the 3 group  (7 animals), aftewr one month from the beginning diet were orally receiving quercetin (50 mg / kg) five times per week for 30 days. The combined effect of the epitheliotropic toxicant delagil, a chronic emotional pain syndrome with alimentary polyphenolic insufficiency, caused pronounced dystrophic changes in the epithelium and the intrinsic plate of the oral mucosa. Quercetin was the best corrector of inflammatory-destructive changes. The nature of the compensatory-regenerative processes in the cells of the epithelial layer acquired features inherent in the intact group. Quercetin prevented the oppression of proliferative activity of the epithelium.